On the Existence of Periodic Solutions of Nonlinear Difference Equations - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We obtain new sufficient conditions for the existence and uniqueness of an N-periodic solution (N is a positive integer) of a nonlinear difference equation with continuous argument of the form x(t + 1) = f(x(t)) and investigate the properties of this solution.